Sami yoik, Sami history, Sami health: a narrative review - Hämäläinen, Soile; Musial, Frauke; Salamonsen, Anita; Graff, Ola; Olsen, Torjer A. (International Journal of Circumpolar Health, 2018)
Music as a possible health-promoting agent has attained increasing academic and scientific interest over the last decades. Nonetheless, possible connections between indigenous singing traditions and health beyond traditional ceremonial healing practices are still under-researched worldwide. The Sami, the indigenous people living in Northern Fennoscandia, have a distinct ancient vocal music tradition called “yoik” practiced from immemorial times. The Sami share a history of assimilation with many indigenous people. During this period of nearly 400 years, yoik alongside other cultural markers was under hard pressure and even banned at times. Compared to other indigenous people in the Arctic, Sami public health shows few significant unfavourable differences to the majority population. The potential role of yoik as a protective health and resilience factor within the Sami culture is the topic of this review. We suggest a two stage model for the health promoting effects of yoik through i) emotion regulation and stress relief on the level of the individual, and ii) as a socio-cultural resilience factors within the Sami population. This review is to be understood as theory-building review article striving for a scholarly review of the literature.